Ciudad solle: pistas histórico-culturales para representar la memoria y la identidad en las prácticas del consumo mediático de la música-mundo en Cartagena (Colombia) (2010)
ResumenDesde una perspectiva cultural popular se pretende reconstruiruna memoria de recepción radial y su relación con la música-mundo(vista desde su sentido periférico). A partir de la historia de vida sefacilitó la emergencia de pistas que documentan la construcción deuna identidad juvenil, que integró «lo ajeno» reelaborándose con«lo propio», en las décadas de los setenta y ochenta en Cartagena. Setrata de dar cuenta de un fenómeno de hibridación entre elementoslocales y globales. En ese sentido se describe, analiza e interpreta laexperiencia del cambio en los procesos de identidad en relación conel consumo cultural de la radio y otros medios.AbstractDrawing on notions of popular culture, this study is an attempt to explorereception processes and their relationship with world-music, understood asthe interaction of local and foreign music in a given cultural context. Basedon a the life story of a «solle»-a label given to young people in popular areas of Cartagena in the 70s and 80s- the authors reflect upon the construction of youth identity, including the incorporation of the «foreign» and how it is merged with what is perceived as «local». There is also an attempt to report on a process of hybridization between local and global elements. The authors describe, analyze and interpret the experience of change in the construction of youth identity in relation to cultural consumption of radio, and to a lesser extent of other media.